2018
DOI: 10.1128/aem.02830-17
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bacteria and Methanogens To Understand the Role of Residual Slurry as an Inoculant in Stored Liquid Dairy Manure

Abstract: Microbial communities in residual slurry left after removal of stored liquid dairy manure have been presumed to increase methane emission during new storage, but these microbes have not been studied. While actual manure storage tanks are filled gradually, pilot- and farm-scale studies on methane emissions from such systems often use a batch approach. In this study, six pilot-scale outdoor storage tanks with (10% and 20%) and without residual slurry were filled (gradually or in batch) with fresh dairy manure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 65 publications
(82 reference statements)
5
28
1
2
Order By: Relevance
“…Throughout the storage period, CH 4 fluxes from acidified slurries remained low, consistent with levels observed during the lag phase (the first 20 days of storage, Figure 1C ). The lag phase observed in the current study was also observed in our previous studies that did not involve acidification ( Habtewold et al, 2018 ). A previous study from our lab has linked shifts in methanogens to methane emissions ( Habtewold et al, 2018 ), therefore we predicted that the communities would shift after acidification.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Throughout the storage period, CH 4 fluxes from acidified slurries remained low, consistent with levels observed during the lag phase (the first 20 days of storage, Figure 1C ). The lag phase observed in the current study was also observed in our previous studies that did not involve acidification ( Habtewold et al, 2018 ). A previous study from our lab has linked shifts in methanogens to methane emissions ( Habtewold et al, 2018 ), therefore we predicted that the communities would shift after acidification.…”
Section: Discussionsupporting
confidence: 90%
“…The lag phase observed in the current study was also observed in our previous studies that did not involve acidification ( Habtewold et al, 2018 ). A previous study from our lab has linked shifts in methanogens to methane emissions ( Habtewold et al, 2018 ), therefore we predicted that the communities would shift after acidification. Using qPCR-based quantification and deep sequencing (Illumina MiSeq) of phylogenetic and functional marker genes and transcripts, we demonstrated that slurry acidification (to pH 5.9) did not affect the community structure of most anaerobically-degrading microorganisms except methanogens closely related to the genus Methanosarcina .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations